1137 Sleep Duration, Physical Activity And Cognitive Decline In Chinese Older Adults: Findings From The CHARLS. (27th May 2020) - Li, J; Alfini, A J; Yu, F; Schrack, J A; Cotter, V; Taylor, J L; Spira, A P
Abstract: Introduction: Lack of physical activity and disturbed sleep have been linked to older adult's poor cognitive outcomes; however, little is unknown how they interact to affect cognition long-term. The purpose of this study was to examine the association of baseline sleep duration and physical activity (PA) with change in cognition independently and interactively over four years. Methods: The sample included 1126 community-dwelling older adults aged 60+ (mean age 67.1±5.9 years, 51% female) from the 2011 baseline and 2015 follow-up data of the China Health and Retirement Longitudinal Study (CHARLS). All variables were assessed through interviews. Sleep duration was measured with hours per 30-minute interval and categorized as very-short (<5h), short (5-6.5h), normal (7-8.5h), and long (≥9h). PA was calculated based on PA intensity, duration, and number of days. Cognition was a composite score of mental capacity, episodic memory, and visuospatial abilities. Data were analyzed using multiple regression (primary outcome: change in cognition; main independent variables: baseline sleep, PA, and sleep PA interaction). Results: At baseline, 19% of participants had very-short sleep duration, 34.4% had short sleep, 39.2% had normal sleep, and 7.2% had long sleep. At follow-up, 57.5% of participants experienced cognitive decline (-3.5±2.5). After controlling for age, gender, education, region, body mass index, smoking, drinking, number of chronic conditions, pain, depression, and cognition at baseline, compared to participants reporting 7-8.5h sleep, those with ≥9h sleep had significantly greater decline in cognition [β=-1.4, 95% CI=2.4, -0.4], while those with <5h sleep [β=-0.5, 95% CI=-1.2, 0.2] and 5-6.5h sleep did not [β=-0.1, 95% CI=-0.7, 0.5]. PA was neither associated with cognitive decline, nor moderated the relationship between sleep duration and cognitive decline. Conclusion: Long sleep might be a marker of cognitive decline in older adults. Prospective analysis, using objectively measured PA and sleep should be conducted to further examine these associations. Support: National Institute of Nursing Research R00NR016484